PENDIDIKAN INKLUSIF DARI PESANTREN - Huda, Anwari Nuril (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ar-Raudlatul Hasanah, Medan, 2018)
Since the last decade, the Indonesian education system has undergone a significant orientation change, namely from segregation education towards towards inclusive education that strives to provide education services for people with disabilities in regular education institutions (non-SLB). In many public education institutions, the implementation of inclusive education experiences paradigmatic and technical constraints, which has implications for the low process of transforming institutions into an inclusive education system. On the other hand, Indonesia has an Pesantren as institution that has proven to be able to play a strategic role in the history of education. The institution also holds a lot of potential that can be used as a basic material for building inclusive education. Through its wealth, pesantren can design inclusive education quickly, distinctively and classically.